Improving Students’ Vocabulary Mastery Through Lyricstraining.com at English Education Department of Halu Oleo University - Utami, Ni Luh Nadya Laksmi; Hanna, Hanna; Kamaluddin, Kamaluddin (Journal of Teaching of English, 2021)
The problem of vocabulary learning for the students is their ability in using words is not quite right. Another problem is the students’ acquisition of the meaning of a word still less. That is why the vocabulary mastery is needed for the students to improve their vocabulary ability. While when teacher teach vocabulary there is not enough media that they can use. Because of that reason, the purpose of this research was to know whether the use of Lyricstraining.com improve students’ vocabulary mastery at English Education Department of Halu Oleo University as the media for vocabulary learning.  The subject of this research were 20 students of English education Department of Halu Oleo University who were taking vocabulary class. The method that used on this research was pre experimental with one group pre and post test. The instrument of this research was vocabulary test includes multiple choices and matching words questions. The result of this research showed the improvement of students’ vocabulary mastery after the treatment. This result proved by the incerase of students’ mean score. The mean of students score before the using of Lyricstraining.com  was 73.6. According to the level, it was categorized as good level. After the using of Lyricstraining.com, the mean score of the students was 82.6 and categorized as very good. It means that the mean score of the students on the pre-test and post-test was increased. Furtherrmore based on the finding, H1 was accepted  because  of the  Sig (2 tailed) was 0.000 which was lower than the alpha value α (0.05) or sig (2 tailed) 0.000 < 0.05. In other words the result showed the using of  Lyricstraining.com improve students’ vocabulary mastery at English Education Department of Halu Oleo University.